2023
DOI: 10.36502/2023/asjbccr.6312
|View full text |Cite
|
Sign up to set email alerts
|

Actual Meal of Low Carbohydrate Diet (LCD) for Diabetic Patient Treated by Effective Imeglimin (Twymeeg)

Tomoko Kusumoto,
Hiroshi Bando,
Kenji Hayashi
et al.

Abstract: The case is a 51-year-old male with obesity, type 2 diabetes (T2D), dyslipidemia, and hypertension. His HbA1c value increased to 8.0%, accompanied by oral semaglutide administration. Glucose variability was exacerbated after that, and then novel imeglimin (Twymeeg) was initiated. HbA1c decreased from 7.4% to 6.7% over 4 months with a 3 kg weight reduction. The case also had low back pain (LBP) and lumbar spinal stenosis (LSS), probably resulting from Metabolic syndrome (Met-S), and had actual experience with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Out of several OHAs, imeglimin (Twymeeg) has come into focus for its impressive medical mechanism [14]. The authors and colleagues have experienced and reported effective T2D cases treated by imeglimin [15,16]. Recently, we treated a male T2D patient with some impressive aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Out of several OHAs, imeglimin (Twymeeg) has come into focus for its impressive medical mechanism [14]. The authors and colleagues have experienced and reported effective T2D cases treated by imeglimin [15,16]. Recently, we treated a male T2D patient with some impressive aspects.…”
Section: Introductionmentioning
confidence: 99%
“…In January 2023, the American Diabetes Association (ADA) announced the standard treatment guidelines [1]. Among these recommendations, appropriate diet, oral hypoglycemic agents (OHAs), and insulin administration methods have been advised [2]. Historically, diabetics were once treated by restricting carbohydrate intake [3].…”
Section: Introductionmentioning
confidence: 99%